Teachers ’and students’ attitudes towards using the Tablet PC in learning and teaching in Jordanian schools - Kneibi, Fatinah Mohammed Saber (Arab Journal for Sciences and Research Publishing, 2016)
-The aim of this study was to identify the attitudes of teachers and students towards the use of the Tablet PC in teaching and learning in Jordanian schools. The study followed the qualitative and quantitative approach. Questionnaires and interviews were used to collect data. (143) of the students in the upper grades (eighth, ninth and tenth) in the private schools of the harvest in Amman, selected as a case study for these schools. The iPad is used in learning and teaching. The results of the study showed that the level of attitudes of both teachers and students towards the use of the Tablet PC was moderate, but the students’ attitudes toward their use are more positive than the teachers. Abstract: This study found that teachers’ attitudes towards using the Tablet PC were moderate. Teachers were divided into three categories in terms of the trend toward using the Tablet PC in learning and teaching: a negative trend group and a positive trend category. The third category of teachers The students were more positive than the teachers, and 64% of the students interviewed learned the lessons of using the tablet in learning and teaching.